Anticoagulation management during cross-clamping and bypass. Issue 3 (September 2016) - Lander, H.; Zammert, M.; FitzGerald, D.
Abstract : Anticoagulation is required for successful implementation of cardiopulmonary bypass (CPB), as well as for surgeries requiring temporary aortic occlusion. It is well established that both coagulation and fibrinolysis are activated during CPB (Teufelsbauer et al., 1992) [1]. Appropriate dosing, monitoring, and maintenance of anticoagulation are essential to prevent devastating thrombosis of the CPB circuit or the occluded aorta and to minimize the activation of the hemostatic system. Although numerous novel anticoagulants have been developed over the past decade, unfractionated heparin remains the primary anticoagulant utilized during these types of procedures, with monitoring systems primarily based upon the activated clotting time and/or heparin concentration. This article will review the current state of anticoagulation management during cross-clamp and CPB.